2021
DOI: 10.1108/pr-05-2020-0340
|View full text |Cite
|
Sign up to set email alerts
|

Investigating leadership and employee well-being in higher education

Abstract: PurposeThis article aims to understand the underlying mechanisms through which transformational leadership influences employee job satisfaction and turnover intentions. Specifically, the study explores the mediation role of employee well-being on the relationships between leadership and both employee job satisfaction and turnover intentions.Design/methodology/approachEmploying a quantitative research method, data were collected from 280 academics and professional staff from an Australian regional university. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 73 publications
2
25
0
2
Order By: Relevance
“…The results of the current study are consistent with the studies by Ma and Jiang (2018) and Gilbert and Kelloway (2018) that suggest that transactional leadership is positively linked to the innovative behaviour and well-being of employees. The findings are also consistent with the study of (Samad, Muchiri, & Shahid, 2021), there results showed a significant association between transformational leadership and employee well-being and job satisfaction which proves that employees working under such leaders are satisfied with their jobs and possess better mental health, also such employees do not want to leave their workplace thus there is reduced turnover.…”
Section: Discussionsupporting
confidence: 89%
“…The results of the current study are consistent with the studies by Ma and Jiang (2018) and Gilbert and Kelloway (2018) that suggest that transactional leadership is positively linked to the innovative behaviour and well-being of employees. The findings are also consistent with the study of (Samad, Muchiri, & Shahid, 2021), there results showed a significant association between transformational leadership and employee well-being and job satisfaction which proves that employees working under such leaders are satisfied with their jobs and possess better mental health, also such employees do not want to leave their workplace thus there is reduced turnover.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the literature is still in its infancy and has not fully examined how leadership practices affect subordinates' JC (Hetland et al, 2018;Kim & Beehr, 2018;Afsar et al, 2019). Additionally, some previous studies revealed that TL was linked to employee wellbeing (McMurray et al, 2010;Samad et al, 2021). However, to the authors' knowledge, none of them examined the sequential mediating effects of PE and JC.…”
Section: -Introductionmentioning
confidence: 90%
“…Due to the powerful position of managers and supervisors in the organization, they can influence EW in many ways. For example, negative management behaviors can contribute to employment stress, poor work performance, illness, job dissatisfaction, rotation, anxiety, and depression (Samad et al, 2021).…”
Section: Transformational Leadership and Employee Wellbeingmentioning
confidence: 99%
“…Dilihat dari hasil uji hipotesis pertama (H1), kepemimpinan transformasional dan employee wellbeing berpengaruh secara signifikan (t-statistic 2.475 > 1.96 dan p-value 0.014 < 0.05) dan bersifat positif (β bernilai 0.477). Sesuai dengan pernyataan dari Samad et al (2021) yang saat itu meneliti akademisi dan para staf profesional dari universitas regional Australia, membuktikan bahwa semakin karyawan mempresepsikan pemimpinnya sebagai pemimpin transformasional, semakin karyawan mempersepsikan peningkatan employee well-being dalam suatu perusahaan. Dari hasil uji hipotesis kedua (H2), pelatihan sumber daya manusia berpengaruh signifikan terhadap employee well-being (tstatistic 2,103 > 1.96 dan p-value 0.036 < 0.05) dan bersifat positif (β bernilai 0.416).…”
Section: Hasil Dan Pembahasanunclassified
“…Pemimpin transformasional biasanya akan mempertimbangan dan peduli dengan kekhawatiran dan pertimbangan para pekerjanya. Samad et al (2021) menjelaskan kepemimpinan transformasional memiliki empat dimensi, yaitu: (1) pertimbangan individual, (2) stimulasi intelektual, (3) motivasi inspirasional, dan (4) pengaruh ideal. Oleh karena itu, seluruh dimensi ini perlu diperhatikan dengan cermat dan diimplementasikan dengan baik.…”
unclassified